Current noise in resonance tunnel diodes based on InGaAlAs heterostructures - Figueiredo, J. M. L. (2012)
Noise in resonance tunnel diodes based on InGaAlAs structures is studied at two frequencies. A shot noise caused by the current flowing through two barriers of the heterostructure is identified. It was found that if the voltage across the structure is within the first ascending section of the current–voltage characteristics, the shot noise is suppressed with the suppression ratio G ~ 1/15. In the second ascending section of the current– voltage characteristic, the shot noise coincides with the shot noise of electrons passing through one barrier ( G = 1) by the order of magnitude. The specific features of current flow affecting the behavior of noise in the resonance tunnel structures are discussed.